Force Myography Shows Higher Correlation to Force Output Compared to Average Rectified Value Electromyography Features - Sierotowicz, Marek; Castellini, Claudio; Anam, Khairul (Springer Science and Business Media Deutschland GmbH, 2025)
Compared to surface electromyography, force myography, or FMG, setups can be very cost-effective and robust, and they offer the advantage of not requiring skin contact. FMG as a modality is inherently correlated with muscular force, and should by extension be more directly correlated with measurable net force output in healthy subjects as well. In this study, we set out to prove this hypothesis by comparing the performance of a regression algorithm predicting isometric finger pressure based on FMG, as opposed to electromyography. Additionally, we demonstrated the effectiveness of a low-cost system, which concurrently with the robustness of FMG sensors, would make them an attractive solution to be used in resource-constrained settings, thus fostering a more widespread adoption of electronic prostheses in low- and middle income countries.
CRIS-Team Scopus Importer:2025-03-28